EUPHEMISM IN THE 2024 INDONESIAN VICE-PRESIDENTIAL DEBATE - Muhammad Saibani Wiyanto; Fitri Amalia Damayanti; Suparti; Adib Darmawan (LPPM Universitas PGRI Jombang, 2026)
This research investigates the use of euphemisms in the vice-presidential debates during the 2024 general election in Indonesia. Through a qualitative case study approach, the study analyzes how vice-presidential candidates, including Gibran Rakabuming, Muhaimin Iskandar, and Mahfud MD, utilize various forms of euphemisms to influence public perception, avoid controversy, and effectively communicate their policies. The findings reveal that candidates frequently employ politeness euphemisms, understatement euphemisms, softening euphemisms, evasive euphemisms, and formality euphemisms. These linguistic strategies help candidates navigate sensitive topics, present their policies in a more favorable light, and maintain their credibility with the electorate. The strategic use of euphemisms highlights the importance of language in political communication and its impact on shaping public opinion.